The Role of Metacognitive Scaffolding in Fostering Creative Thinking and Conceptual Mastery in Physics: A Comparative Study Across Educational Level - Noke Kesaulya; Parno; Endang Purwaningsih; Sunaryono (Jurnal Penelitian Pendidikan IPA, 2025)
The study explores the importance of concept mastery in physics education for developing 21-st century skills, focusing on the role of metacognitive scaffolding in enhancing creative thinking. Data were collected from publications indexed by Google Scholar over the past 10 years from 2015 to 2025, using the Publish or Perish tool. Through a systematic literature review using PRISMA guidelines, data from Google Scholar was analyzed using VOSviewer software, covering publication types, sources, and frequently occurring keywords in related studies. In-depth analysis of several key articles indicates that metacognitive scaffolding has a significant positive impact on enhancing student’s creative thinking abilities and concept mastery at different educational levels, supported by the role of teachers. However, there is a potential decline in similar research seen in publications related to physics concepts mastery and creative thinking, which trends to decrease in 2025. Key themes include metacognitive scaffolding, critical thinking, concept mastery, and physics education in various educational levels.